Two new species of the genus Zhengitettix (Orthoptera: Tetrigidae: Scelimeninae) from China - Chen, Ya-Zhen; Deng, Wei-An (Zootaxa, 2022)
New species, Zhengitettix convexa Deng , sp. nov. from Yunnan and Zhengitettix fengyangshana Deng, sp. nov. from Zhejiang, are described and illustrated. Z. convexa can be easily distinguished from other species of the genus by the disc of pronotum slightly convex between shoulders and interspersed with sparse carinae on the protuberance, slightly concave behind shoulders. Z. fengyangshana is similar to Z. transpicula Zheng & Jiang, 2002, but differs in narrow frontal ridge, with interhumeral carinae, shape of median carina of pronotum and posterior angles of pronotal lateral lobes. An updated key to all species of the genus Zhengitettix is given.